Establishment of a New Qualitative Evaluation Method for Articular Cartilage by Dynamic T2w MRI Using a Novel Contrast Medium as a Water Tracer. (September 2022) - Hosokawa, Yoshiaki; Onodera, Tomohiro; Homan, Kentaro; Yamaguchi, Jun; Kudo, Kohsuke; Kameda, Hiroyuki; Sugimori, Hiroyuki; Iwasaki, Norimasa
Objective: In the early stages of cartilage damage, diagnostic methods focusing on the mechanism of maintaining the hydrostatic pressure of cartilage are thought to be useful. 17 O-labeled water, which is a stable isotope of oxygen, has the advantage of no radiation exposure or allergic reactions and can be detected by magnetic resonance imaging (MRI). This study aimed to evaluate MRI images using 17 O-labeled water in a rabbit model. Design: Contrast MRI with 17 O-labeled water and macroscopic and histological evaluations were performed 4 and 8 weeks after anterior cruciate ligament transection surgery in rabbits. A total of 18 T2-weighted images were acquired, and 17 O-labeled water was manually administered on the third scan. The 17 O concentration in each phase was calculated from the signal intensity at the articular cartilage. Macroscopic and histological grades were evaluated and compared with the 17 O concentration. Results: An increase in 17 O concentration in the macroscopic and histologically injured areas was observed by MRI. Macroscopic evaluation showed that the 17 O concentration significantly increased in the damaged site group. Histological evaluations also showed that 17 O concentrations significantly increased at 36 minutes 30 seconds after initiating MRI scanning in the Osteoarthritis Research Society International (OARSI) grade 3 (0.493 in grade 0, 0.659 in grade 1, 0.4651 in grade 2, and 0.9964 in grade 3, P < 0.05). Conclusion: 17 O-labeled water could visualize earlier articular cartilage damage, which is difficult to detect by conventional methods.